Managing Geostrategic Issues 2019
DOI: 10.26493/978-961-6832-68-7.13
|View full text |Cite
|
Sign up to set email alerts
|

Customer Value Creation in the Financial Services Industry

Abstract: Financial technology (fintech) -as the recent technology driven digital transformational force in the financial services industry -is a currently popular research topic amongst academic and practical experts. The research area has many directions, however, the authors identified that there is a lack in the existing academic literature regarding the customer value creation power of the fintech novelties. Customer value as a term appeared at the end of the 20th century in the strategic management and marketing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Ref. [59] defines customer enablement as an organizational endeavor dedicated to equipping customers with essential tools and knowledge to maximize the value customers derive from a business's offerings. This innovative approach not only augments customer experience but also cultivates self-sufficiency, surpassing conventional customer support paradigms.…”
Section: Customer Enablement (Ce)mentioning
confidence: 99%
“…Ref. [59] defines customer enablement as an organizational endeavor dedicated to equipping customers with essential tools and knowledge to maximize the value customers derive from a business's offerings. This innovative approach not only augments customer experience but also cultivates self-sufficiency, surpassing conventional customer support paradigms.…”
Section: Customer Enablement (Ce)mentioning
confidence: 99%
“…Many FinTech studies (Arha & Jufri, 2020;Jutla & Sundararajan, 2016;Lee & Shin, 2018;Varga, 2017) explored the FinTech value drivers, ecosystem, and its elements, while Csepy & Aranyossy (2019) were focusing on the customer value creation power in the financial services industry. Although Phat Pham et al (2021) categorized FinTech as "bank FinTech" (traditional financial institutions utilizing financial technologies) and as "Fin-Tech-outside" (non-financial institutes using technology to provide financial services) -which viewpoint and sector-specific analysis also assessed by other authors (Gyüre, 2020;Horváth, 2019Horváth, , 2020Kerényi & Molnár, 2017) -, it can be concluded that the definition of Fin-Tech is very versatile and can be approached from many sides.…”
Section: Figure 3 the Everythingtech Phenomenon In Various Industriesmentioning
confidence: 99%